TEOLOGIA W SŁUŻBIE WIARY – REFLEKSJA NAD LEKTURĄ KATECHEZY BENEDYKTA XVI „RADOŚĆ WIARY” - Jerzy Lewandowski (Studia Theologica Varsaviensia)
In a contemporary, secularized society, faith is undervalued and marginalized. How can we find the “joy of faith” nowadays? A deepening response to this question is found in “Joy of Faith,” which is a type of catechesis by Pope Benedict